2022
DOI: 10.1111/exd.14709
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and pathogenesis of Koebner phenomenon

Abstract: The Koebner phenomenon, also known as isomorphic reaction, refers to the development of secondary lesions with the same clinical manifestations and histopathological characteristics as the primary lesions in normal skin after trauma or other stimuli. The triggering factors of Koebner phenomenon include physical trauma, chemical stimulation, mechanical stress, iatrogenic stimulation and pathogenic infection. Vitiligo, psoriasis and lichen planus are considered true Koebner phenomenon. Recent studies have shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 166 publications
0
26
0
Order By: Relevance
“…23 The vulva is exposed to numerous koebnerizing events to include minor surgery, sexual friction, hair management, and contact dermatitis. 23,24 A subtype of koebnerization is the Wolf isotopic response, defined as the appearance of a new dermatosis in the same place as an unrelated lesion, initially described as infections or immune disorders within resolving herpes zoster. 25 The tricolor vulva of psoriasis superimposed on vitiligo may represent a Wolf response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 The vulva is exposed to numerous koebnerizing events to include minor surgery, sexual friction, hair management, and contact dermatitis. 23,24 A subtype of koebnerization is the Wolf isotopic response, defined as the appearance of a new dermatosis in the same place as an unrelated lesion, initially described as infections or immune disorders within resolving herpes zoster. 25 The tricolor vulva of psoriasis superimposed on vitiligo may represent a Wolf response.…”
Section: Discussionmentioning
confidence: 99%
“…The Koebner phenomenon describes initiation or provocation of skin conditions in an injured area of previously healthy skin, first described in psoriasis but also documented in LS, LP, and vitiligo 23 . The vulva is exposed to numerous koebnerizing events to include minor surgery, sexual friction, hair management, and contact dermatitis 23,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,28 Trauma is also a known trigger of both palmoplantar psoriasis and ACH. 29,30 IL36 is involved in epidermal inflammation underlying Koebnerization, 31,32 and is up-regulated following mechanical stimulation in a variety of tissues. 33,34 In murine models, transgenic IL36α expression resulted in epidermal hyperplasia and hyperkeratosis, 35 which were further aggravated in Il36rn −/− mice, an established animal model of DITRA.…”
Section: Con Clus I On S and Per S Pec Tive Smentioning
confidence: 99%
“…While the infiltration of immune cells into skin plays a critical role in the development of psoriasis, as evidenced by interleukin (IL) -23/IL-17 axis (Fitch, Harper, Skorcheva, Kurtz, & Blauvelt, 2007; Hawkes, Yan, Chan, & Krueger, 2018; Kim & Krueger, 2017), recent studies have revealed that cells constructing skin structure, such as keratinocytes, fibroblasts, and endothelial cells, also play pivotal roles in the development (Heidenreich, Röcken, & Ghoreschi, 2009; Lowes, Russell, Martin, Towne, & Krueger, 2013; Zhang et al, 2023) and maintenance (Arasa et al, 2019; Francis et al, 2024; Li et al, 2023; Ma et al, 2023; Tan et al, 2015; Zhu et al, 2020) of psoriasis. Among these cells, keratinocytes function as a barrier and produce cytokines, chemokines, and antimicrobial peptides against foreign stimuli, resulting in the activation of immune cells (Ni & Lai, 2020; Zhou, Chen, Cui, Shi, & Guo, 2022).…”
Section: Introductionmentioning
confidence: 99%